Increased Risk of Influenza-Like Illness Clusters in Schools, Taiwan from 2011 to 2020: A Retrospective Study - Yu-Ching Chou; Fu-Huang Lin; Chi-Jeng Hsieh; Chia-Peng Yu (Journal of Epidemiology and Global Health)
Abstract Acute influenza-like illnesses (ILIs) are primarily caused by influenza type A or type B viruses. Several factors influence the risk of the spread of ILIs. The present study investigated the epidemiological characteristics, differences, and epidemiological trends of influenza viruses, noninfluenza respiratory pathogens, and locations where clusters occurred in Taiwan between 2011 and 2020. The study analyzed publicly available data on 1,545 confirmed ILI clusters, with the data obtained from the Taiwan Centers for Disease Control. In total, 1,334 ILI clusters were caused by influenza virus infection, 11 ILI clusters were caused by noninfluenza respiratory pathogens, and 78 ILI clusters were caused by pathogens not detected in routine testing. Additionally, for 122 ILI clusters, no pathogen detection was initiated. Significant differences were observed (p < 0.001) in the number of ILI clusters between influenza and noninfluenza respiratory pathogens in 2011–2020. In addition, significant differences were observed (p < 0.001) in the number of ILI clusters between locations in 2011–2020. In terms of specific pathogens within ILI clusters, single infections with influenza A virus accounted for the highest number of cases (69.6%, 1076/1358, odds ratio: 1.740–2.957, p < 0.001–0.012), followed by adenovirus infections among noninfluenza respiratory pathogens (58.3%, 7/12). Schools had the highest number of ILI clusters (47.3%, 731/1545) among the investigated institutions (odds ratio: 1.438–1.556, p < 0.001–0.012). This study provides valuable insights into ILI cluster transmission patterns in Taiwan over a 10-year period and highlights the importance of long-term studies covering a wide geographic area as a means of understanding the implications of such patterns.